One Health Integration to Control and Prevent Zoonoses: Application of Organizational Theory Literature - Lisset M Dumet Poma; Sherril Gelmon; Julia M. Goodman; Seth E. O’Neal (Hatfield Graduate Journal of Public Affairs)
Zoonoses are infectious diseases transmitted between animals and people that disproportionately affect low- and middle-income countries (LMICs). The One Health (OH) approach aims to integrate systems, incentivizing collaboration among animal, human, and environmental systems to address zoonoses and improve health. Innovative solutions for effectively and sustainably achieving systems integration are needed. Organizational theories can facilitate the study of the context of OH implementation, applying comprehensive approaches that recognize the interconnections among organisms, the environment, and social systems, including the diverse entities needing integration (e.g., policy, community, public organizations). This narrative review examines organization and systems literature to provide recommendations for studying the context of OH implementation and integration solutions with implications for research in LMICs. First, we review the concepts of complexity and systems thinking. We describe contingency theory and open systems theory, including the concepts of differentiation and fragmentation, to explain the influence of the environment on the structures of organizations involved in OH implementation. The sociological aspect of organizations is introduced with institutional theory, and recommendations of integration mechanisms for OH are summarized. Finally, we explain the concept of governance for health and provide recommendations for the application of governance theories in the context of LMICs.